2017
DOI: 10.1016/j.gendis.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to detect bacterial resistance to disinfectants

Abstract: In clinical practice, the important hygienic prevention of bacterial pathogen spread is disinfection of potentially contaminated area. Benzalkonium bromide and chlorhexidine acetate are commonly used disinfectants with a broad spectrum of anti-microbial effect. It is vital to inhibit the spread of pathogen in hospital. However, a large number of pathogens with the decreased antiseptic susceptibility have been isolated from clinical samples which showed an increased minimal inhibitory concentration (MIC) agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Unfortunately, it has been observed that the addition of these compounds could correlate with the emergence of resistant strains to antibiotics and disinfectants. Further research, therefore, is required to test new compounds [59, 60]. Epinecidin-1 is one of the few AMPs in which the efficiency has been evaluated as a part of the cleaning solution.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, it has been observed that the addition of these compounds could correlate with the emergence of resistant strains to antibiotics and disinfectants. Further research, therefore, is required to test new compounds [59, 60]. Epinecidin-1 is one of the few AMPs in which the efficiency has been evaluated as a part of the cleaning solution.…”
Section: Resultsmentioning
confidence: 99%
“…The increasing rate of bacteria resistant to antibiotics and antiseptics poses a major problem to human and veterinary health. Consequently, there is a desperate demand for novel antimicrobial agents active against resistant bacteria ( 8 , 12 , 29 ). In recognition of this requirement, this study investigated alternative antimicrobial compounds that might be suitable for the prevention of bovine mastitis.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of antimicrobial agents used for these purposes include iodine-based products, which are most often used as an antiseptic for teat disinfection ( 10 ), but also various products containing phenolics, alcohol or chlorhexidine as germicides ( 11 ). However, it has been reported that in addition to antibiotic resistance, bacteria are less susceptible to commonly used antiseptics, e.g., chlorhexidine, benzalkonium chloride or povidone-iodine ( 12 ). Additionally, a high prevalence of genes responsible for benzalkonium chloride- and chlorhexidine-resistances has also been discovered in human S. aureus isolates ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Benzalkonium bromide, a quaternary ammonium compounds, is wildly used as disinfectant for sterilization of non-living objects or surfaces (He et al, 2017). The usage of this disinfectant is the vital way to inhibit the spread of pathogens.…”
Section: Inactivation Efficacy Of Peroxyacetic Acid Solution Against mentioning
confidence: 99%